STUDENTS’ NUMERACY SKILLS IN GEOMETRIC SEQUENCES AND SERIES: A CASE STUDY BASED ON LEARNING MOTIVATION - Fikriyati, Adzkia; Hendriana, Benny (Journal of Authentic Research on Mathematics Education (JARME), 2025)
Literacy and numeracy are both very important abilities to support students' academic success and future life skills. This study aims to analyze the numeracy skills of vocational students in terms of learning motivation. The method used in this research is descriptive qualitative method. This research was conducted at SMKS Malaka by involving 53 students in grades X and 6 as subjects in this study, each of which represents high, medium, and low motivation levels. The instruments used are ability tests, motivation questionnaires, interviews used to explore more in-depth information about students' strategies, obstacles and attitudes in solving mathematics. Based on the results of this study, it shows that students with high and medium levels of learning motivation can meet the indicators, namely being able to implement various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of daily life, analyze the information presented, and interpret the results of the analysis to predict and make decisions. Whereas students with low levels of motivation can only fulfill one indicator, namely only being able to interpret various numbers and symbols related to basic mathematics.